Wazzyjump - Moniz, Michael (Simply Read Books, 2011)
Wazzyjump is a magical rabbit, but no one knows what his magic is. Lion, ruler of all the beasts, wants to steal Wazzyjump's magic for himself, and so does tricky Fox. But Wazzyjump has a special magic that can be had but cannot be stolen.